2015
DOI: 10.1016/j.jamcollsurg.2014.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care Delivered Before vs After a Quality-Improvement Intervention for Acute Geriatric Trauma

Abstract: Background Older trauma injury patients had improved recovery after we implemented routine geriatric consultation for patients ≥ age 65 at a level-1 academic trauma center. The intervention aimed to improve quality of geriatric care. However, the specific care processes that improved are unknown. Study Design Prospective observation comparing medical care after (December 2007-November 2009) versus before (December 2006-November 2007) implementation of the geriatric consult-based intervention. To measure qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Established models of care (such as the Hospital Elder Life Program 18 ) and geriatric comanagement strategies focus on simple interventions, such as frequent reorientation, hydration, and early ambulation to prevent delirium, deconditioning, and malnutrition. 19,20 Length of stay was a significant risk factor for LOI, with each additional hospital day adding 30% risk. Certainly, deconditioning over the hospital stay is a logical mechanism that may explain LOI.…”
Section: Discussionmentioning
confidence: 99%
“…Established models of care (such as the Hospital Elder Life Program 18 ) and geriatric comanagement strategies focus on simple interventions, such as frequent reorientation, hydration, and early ambulation to prevent delirium, deconditioning, and malnutrition. 19,20 Length of stay was a significant risk factor for LOI, with each additional hospital day adding 30% risk. Certainly, deconditioning over the hospital stay is a logical mechanism that may explain LOI.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the difficulties in having geriatricians assess every older trauma patient (geriatric consultation rates in the prior studies range from 40–69% of all older trauma patients), 7,8,10 we focused our care model on older adults with geriatric syndromes or specific needs. The TQIP guidelines suggest using the Identifying Seniors at Risk tool (ISAR), which has been evaluated in other settings for identifying higher risk patients for likelihood of functional decline or poor long-term outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…6 A quality of care evaluation, measured by the Assessing Care of Vulnerable Elders (ACOVE) validated quality measures, found an increase in quality with geriatric consultation. 7 However the aggregate of ACOVE quality measures does not include many quality measures of high importance to trauma surgeons, such as mortality, discharge to skilled nursing facilities, or code status. Another evaluation of a geriatric consultation model found that geriatricians decreased length of stay and decreased discharge to skilled nursing facilities for older adult trauma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the quality of care and functional outcome of elderly trauma patients were found to improve when geriatric consultation was implemented. 10,11 The establishment of a geriatric trauma service for patients at least 60 years old resulted in a decrease in the average emergency department (ED) length of stay, average ED to operating room time, average surgical intensive care unit length of stay, and average hospital length of stay. 12 Moreover, the rates of mortality, pneumonia, respiratory failure, and urinary tract infections decreased.…”
Section: Toivari Et Almentioning
confidence: 99%